The Use Of Quizizz Mastery Peak Media In Increasing Student Learning Motivation In Islamic Education Classes In Class XI TJKT 2 At SMKN 1 Purwakarta - Nurhaeni Nurhaeni; M. Rizik Alfajri; Amelia Putri; Lutfiah Khoerunnida; Deden Dinar; Muhammad Syabani Ridwanulloh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the increase in student learning motivation through the use of Quizizz Mastery Peak media in Islamic Religious Education (PAI) learning in class XI TJKT 2 SMKN 1 Purwakarta. This study is a Classroom Action Research (CAR) conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. The results of the study indicate that the Quizizz Mastery Peak media has a positive impact on increasing student learning motivation, as indicated by an increase in motivation scores from cycle I to cycle II. This media creates a fun, interactive, and competitive learning atmosphere.